A metabolic link between the urea cycle and cancer cell proliferation. (3rd March 2016) - Nagamani, Sandesh C.S.; Erez, Ayelet
ABSTRACT: Clinical observations in citrullinemia type I, an inborn error of metabolism, led us to explore the benefits of somatic ASS1 silencing in cancer. We found that downregulation of ASS1 results in preferential utilization of its substrate, aspartate, for pyrimidine synthesis to support cell proliferation. Reducing aspartate availability for pyrimidine synthesis restricted cancerous proliferation.